Perpetua's passions : multidisciplinary approaches to the Passio Perpetuae et Felicitatis - Bremmer, Jan N.; Formisano, Marco (Oxford University Press, 2012)
Perpetua's Passions is a collection of studies about Perpetua, a young female Christian martyr who was executed in 203 AD. Like her spiritual guide, Saturus, Perpetua left a diary, and a few years after their deaths a fellow Christian collected these writings and supplied them with an introduction and epilogue: the so-called Passion of Perpetua. The result is one of the most fascinating and enigmatic works of antiquity, which the present volume examines from awide range of perspectives: literary, narratological, historical, religious, psychological, and philosophical viewpoints follow upon a n.